Characteristics and Antimicrobial Properties of Active Edible Films Based on Pectin and Nanochitosan - Thi Minh Phuong Ngo (2020)
This study was aimed at creating new films and determine some functional packaging properties of pectin:nanochitosan films with ratios of pectin:nanochitosan (P:NSC) of 100:0; 75:25; 50:50; 25:75 and 0:100 (%w/w). The effects of the proportions of pectin:nanochitosan incorporation on the thickness, mechanical properties, water vapor permeability, water-solubility, and oxygen permeability were investigated. The microstructural studies were done using scanning electron microscopy (SEM). The interactions between pectin and nanochitosan were elucidated by Attenuated total reflectance-Fourier transform infrared (ATR-FTIR). The results showed that the blending of pectin with nanochitosan at proportions of 50:50 increased the tensile strength to 8.96 MPa, reduced the water solubility to 37.5%, water vapor permeability to 0.2052 g·mm/m2·day·kPa, and the oxygen permeability to 47.67 cc·mm/m2·day. The results of the contact angle test indicated that P:NCS films were hydrophobic, especially, pectin:nanochitosan films inhibited the growth of Colletotrichum gloeosporioides, Saccharomyces cerevisiae, Aspergillus niger, and Escherichia coli. So, P:NCS films with a proportion of 50:50 can be used as active films to extend the shelf life of food.